3b-1=-1

Simple and best practice solution for 3b-1=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b-1=-1 equation:


b in (-oo:+oo)

3*b-1 = -1 // + 1

3*b-1+1 = 0

3*b = 0 // : 3

b = 0

b = 0

See similar equations:

| 6+6t=66 | | 5w-1=-36 | | -8+7w=62 | | 6m-1=-1 | | -3n-3=-21 | | 2k+5=7 | | -4d+5=49 | | 8+7a=-48 | | -3m+7=-20 | | 4k-5=39 | | 3a-4=-4 | | 7k+5=68 | | 3(y-6x)=12 | | 7d+9=23 | | 2a-3=19 | | 3b+1=-8 | | -8+7k=69 | | 2b+10=-6 | | -7k+1=-20 | | -4d+4=-32 | | 6k+6=36 | | 10-7b=52 | | -4k+10=-34 | | 5-3d=-13 | | -5m+9=-51 | | -7n-6=-69 | | 2k-7=9 | | -6b+1=-53 | | -2d-9=-13 | | 3+4k=-33 | | 2+4m=2 | | 1-3m=-26 |

Equations solver categories